2020
DOI: 10.1084/jem.20191779
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CLK3 inhibits the progression of cholangiocarcinoma by reprogramming nucleotide metabolism

Abstract: CDC-like kinase 3 (CLK3) is a dual specificity kinase that functions on substrates containing serine/threonine and tyrosine. But its role in human cancer remains unknown. Herein, we demonstrated that CLK3 was significantly up-regulated in cholangiocarcinoma (CCA) and identified a recurrent Q607R somatic substitution that represented a gain-of-function mutation in the CLK3 kinase domain. Gene ontology term enrichment suggested that high CLK3 expression in CCA patients mainly was associated with nucleotide metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…CLK3 contributes to hepatocellular carcinoma [ 226 ], prostate cancer [ 227 ], and cholangiocarcinoma [ 228 ]. CLK3 is abundantly expressed in testis and in spermatozoa.…”
Section: Clks and Human Diseasementioning
confidence: 99%
“…CLK3 contributes to hepatocellular carcinoma [ 226 ], prostate cancer [ 227 ], and cholangiocarcinoma [ 228 ]. CLK3 is abundantly expressed in testis and in spermatozoa.…”
Section: Clks and Human Diseasementioning
confidence: 99%
“…Moreover, a recent study also found that CDC-like kinase 3 (CLK3) or the cholangiocarcinoma-associated CLK3-Q607R mutant can directly phosphorylate USP13 at Tyr708, and promote its binding to c-Myc (Nayler et al, 1997;Zhou et al, 2020) (Figure 3B). Therefore, this stabilizes c-Myc and activates the transcription of genes related to purine metabolism (Figure 3B).…”
Section: Phosphorylation Regulates the Interactome And Localization Of Dubsmentioning
confidence: 88%
“…Briefly, GC cells with the indicated lentivirus expression plasmid against miR-148b-5p or negative control (scramble) were subcutaneously injected into the flanks of nude mice. After seven weeks, the nude mice were killed through cervical dislocation, and the tumors were measured, and experiments such as western blots and IHC were performed as described previously ( 11 ).…”
Section: Methodsmentioning
confidence: 99%